Dental fluorosis and oral health in the African Esophageal Cancer Corridor: Findings from the Kenya ESCCAPE case–control study and a pan‐African perspective. Issue 1 (12th January 2019) - Menya, Diana; Maina, Stephen K.; Kibosia, Caroline; Kigen, Nicholas; Oduor, Margaret; Some, Fatma; Chumba, David; Ayuo, Paul; Middleton, Daniel R.S.; Osano, Odipo; Abedi‐Ardekani, Behnoush; Schüz, Joachim; et al.
Abstract : There are no studies of oral health in relation to esophageal cancer in Africa, or of Eastern Africa's endemic dental fluorosis, an irreversible enamel hypo‐mineralization due to early‐life excessive fluoride intake. During 2014–18, we conducted a case–control study of squamous cell esophageal cancer in Eldoret, western Kenya. Odds ratios (AORs (95% confidence intervals)) were adjusted for design factors, tobacco, alcohol, ethnicity, education, oral hygiene and missing/decayed teeth. Esophageal cancer cases (N = 430) had poorer oral health and hygiene than controls (N = 440). Compared to no dental fluorosis, moderate/severe fluorosis, which affected 44% of cases, had a crude OR of 20.8 (11.6, 37.4) and on full adjustment was associated with 9.4‐fold (4.6, 19.1) increased risk, whilst mild fluorosis (43% of cases) had an AOR of 2.3 (1.3, 4.0). The prevalence of oral leukoplakia and tooth loss/decay increased with fluorosis severity, and increased cancer risks associated with moderate/severe fluorosis were particularly strong in individuals with more tooth loss/decay. Using a mswaki stick (AOR = 1.7 (1.0, 2.9)) rather than a commercial tooth brush and infrequent tooth brushing also independently increased risk. Geographic variations showed that areas of high esophageal cancer incidence and those of high groundwater fluoride levels have remarkably similar locations across Eastern Africa. In conclusion, poor oral health in combination with, or as a result of, high‐altitude susceptibility to hydro‐geologically influenced dental fluorosis may underlie the striking co‐location of Africa's esophageal cancer corridor with the Rift Valley. The findings call for heightened research into primary prevention opportunities of this highly fatal but common cancer. Abstract : What's new? To date, there are no comprehensive studies of oral health and esophageal cancer in Eastern Africa, nor of this area's endemic dental fluorosis, an irreversible enamel hypo‐mineralization due to early‐life excessive fluoride intake. Here, the authors found that moderate/severe fluorosis is associated with a ten‐fold increased cancer risk in Eastern Africa, particularly if tooth loss or decay is co‐present. The finding is striking because of the remarkable co‐location of Africa's esophageal cancer corridor with areas of high groundwater fluoride. Identification of the causal mechanisms will be critical to primary prevention of this common cancer.